Spacer Effect Caused by Azobenzene System in E/Z Isomerization: An Application for Optical Storage Device - Yuvaraj, A. R.; Tay, Joo Hui; Siti Maznah, Kabeb; Lutfor, M. R.; M. M., Yusoff; Hegde, Gurumurthy (2015)
The spacer effect caused by the system of molecules during the process of E/Z isomerization is reported. The phenomenon was predicted by absorption measurements with UV light of 365nm wavelength was illuminated to the solution of azobenzene dimers with aliphatic and aromatic spacers were incorporated. The photosaturation was observed within 18 seconds for both compounds. But, the dramatic variation in thermal back relaxation is the significant interest in this study. That is Z-E isomerization or thermal back relaxation was occurred around 7-13hours. Here the variation in back relaxation is directly related to the nature of spaced associated with the molecular structure. In particular, the spacer effect is very much important in synthesizing the materials for the optical storage device fabrication.